Expression of the murine norovirus (MNV) ORF1 polyprotein is sufficient to induce apoptosis in a virus-free cell model. - Morgan R Herod; Omar Salim; Rachel J Skilton; Cynthia A Prince; Vernon K Ward; Paul R Lambden; Ian N Clarke (PLoS ONE)
Investigations into human norovirus infection, replication and pathogenesis, as well as the development of potential antiviral agents, have been restricted by the lack of a cell culture system for human norovirus. To date, the optimal cell culture surrogate virus model for studying human norovirus biology is the murine norovirus (MNV). In this report we generate a tetracycline-regulated, inducible eukaryotic cell system expressing the entire MNV ORF1 polyprotein. Once induced, the MNV ORF1 polyprotein was faithfully processed to the six mature non-structural proteins that predominately located to a discrete perinuclear region, as has been observed in active MNV infection. Furthermore, we found that expression of the ORF1 polyprotein alone was sufficient to induce apoptosis, characterised by caspase-9 activation and survivin down-regulation. This cell line provides a valuable new tool for studying MNV ORF1 non-structural protein function, screening for potential antiviral agents and acts as a proof-of-principle for such systems to be developed for human noroviruses.